Coating Design Methods for Railway Transit Themed Trains in Large-scale Sporting Events - MA Shengquan; JIA Xinglong; WANG Chao; WANG Chengtao; WANG Shubin; GUO Hao (Chengshi guidao jiaotong yanjiu)
［Objective］ With the increasing number of large-scale sporting events hosted in China, themed trains have gradually become an important medium for showcasing the image of the host city and the country. Research on the coating design of themed trains aims to enhance the promotional impact of sports through unique designs, reflecting China′s technological and innovative capabilities. ［Method］ Taking the themed train for the 24th Beijing Winter Olympics as an example, design elements are extracted and reconstructed to visualize cultural symbols. This is paired with appropriate coating techniques to ensure that the design meets the requirements for the train′s elongated, unidirectional form and visual stability at high running speeds. The design conveys the Olympic theme, Chinese elements, and cultural characteristics of the Beijing-Zhangjiakou region. The coating design methods from cultural symbols to detailed designs, are summarized and successfully applied to the theme train for the 19th Asian Games in Hangzhou, highlighting Chinese elegance, Zhejiang characteristics, and the charm of Hangzhou. ［Result & Conclusion］ The themed trains designed with this coating method play a significant symbolic role in the context of sporting events, not only enhancing the promotional impact of the events，but also showcasing the innovative achievements of China′s high-speed railway.